Penerapan Algoritma Sattolo Shuffle dalam Sistem Pengacakan Denah Tempat Duduk Peserta Ujian untuk Mencegah Kecurangan Akademik - Surya Darma Nasution; Guidio Leonarde Ginting (Bulletin of Artificial Intelligence, 2025)
Academic cheating during examinations remains a serious problem in educational institutions. One contributing factor is the use of fixed and predictable seating arrangements, which allow exam participants to plan cheating strategies with nearby peers. This study aims to implement the Sattolo Shuffle algorithm in a seating arrangement randomization system for exam participants as a measure to prevent academic dishonesty. The Sattolo Shuffle algorithm was chosen because of its ability to generate cyclic permutations that guarantee every element moves from its original position, ensuring no exam participant occupies the same seat as in a previous exam. The study was conducted using an experimental approach involving 30 exam participants randomized using the Sattolo Shuffle algorithm. The shuffling process requires 29 iterations (n-1 iterations for n=30 elements), and the verification results show that no participant remains in their original position (0 fixed points), proving the algorithm successfully produces a perfect cyclic permutation. All 30 participants form a single cycle, confirming the derangement property of the Sattolo Shuffle algorithm